Academic-Career Counseling Based on the Brain Training Approach - Khadijeh Torki; Maryam Baratali; Zohreh Saadatmand; Zahra Yousefi (Iranian Evolutionary Educational Psychology Journal)
Objective: The objective of this investigation was to conduct academic and career counseling through the lens of a brain training approach. Methods: The present study employs a qualitative research paradigm, specifically utilizing content analysis and a systematic comparative categorization framework. The scope of this research encompasses a comprehensive array of literature and resources pertinent to the domain of curriculum studies, alongside texts and empirical investigations situated within the realm of brain-based education. In light of the extensive assortment of both printed and digital materials, the time frame of 2010 to 2019 has been employed for analysis. The data underwent a tripartite analytical process characterized by open, axial, and selective coding, which were subsequently articulated in a model corresponding to the specified research inquiries. Results: The findings from the analysis indicate that the curriculum counseling framework, informed by the brain training approach, comprises: motivation derived from the brain training methodology - physiological psychology - family counseling utilizing the brain training perspective - academic guidance - career counseling grounded in the brain training approach - assessments of intelligence and aptitude within the context of self-awareness and academic advising - personal development strategies informed by the brain training model - positive psychology as conceptualized through the brain training lens - social psychology framed by the principles of brain training - personality psychology as influenced by the brain training methodology - cognitive psychology informed by the brain training paradigm - and metacognitive psychology based on the brain training approach, alongside considerations of mental health challenges. Conclusions: Overall, the evidence obtained from this study substantiates the significance of a neurocognitive educational methodology in the domains of academic and vocational counseling.